Examining the Impact of Quality Service on Customer Satisfaction in the Emerging Landscape of Online Clothing Retail in Nepal - Manandhar, Raju Bhai; Karki, Tej Bahadur; Manandhar, Erika; Khadka, Kalpana (International Research Journal of MMC, 2024)
Online clothing retailers, both domestic and international, offer a wide range of brands at affordable prices, catering to the preferences of the young generation. This study aims to examine the association and effect of quick delivery service, price quotations, and quality products and services with customer satisfaction in online clothing stores in Nepal. The study employed analytical research designs. The study targeted customers involved in online clothing shopping as the theoretical population. The 140 respondents were selected through snowball sampling. Primary data have been collected by using online questionnaire surveys. The study adopted descriptive statistics like mean, standard deviation, covariance, independent sample t-test, and inferential statistics such as correlation and regression to analyze and interpret the data. This study explored online clothing purchases, finding no significant gender differences in perceptions. Positive correlations between key variables, such as price quotations, quick delivery service, and quality products, suggested their impact on customer satisfaction. Regression analysis confirmed significant associations with customer satisfaction, emphasizing the primacy of product quality and service delivery except pricing. The study recommends prioritizing these factors to boost online clothing sales, highlighting their crucial influence on customer satisfaction in the digital retail landscape.